JavaFX for Dummies - Lowe, Doug (--For dummies., 2015)
This guide gives you access to an innovative software platform that allows you to create and deliver rich Internet applications that can run across a wide variety of connected devices. It highlights the most important features of this powerful graphics platform, giving you the tools to understand it quickly and easily. Doug Lowe brings his experience and passion to this guide, sharing his expert approach to coding using JavaFX. The book shows you how to work with JavaFX controls, how to enhance your scenic design, and also offers advice on how to make a splash with your programs. --